Geo-electrical measurements in environment with presence of underground water - Manevski, Vladimir; Delipetrov, Todor; Delpetrev, Marjan (Geologica Macedonica, 2015)
The coal mine “Suvodol” is chosen for geo-electrical examination because it has been most thoroughlyresearched and has the densest network of mapped boreholes. Through examination of the parameters fromthe boreholes and the geological map of the coal mine we determinate the layered structure of the ore body that providesfavorable conditions for applying the method of geo-electrical sounding. In the process of production of themodels particular attention is given to the level of underground water that has dominant influence in the conductivityproperties of the geological structures.The curves of apparent electrical resistance are interpreted while solving the directtask. For acquiring precise and concrete data while interpreting the synthetic curves it is important to obtain accuratedata for the mapped geological material.